KARAKTERISTIK IMPEDANSI IMPULS NON LINIER PADA PEMBUMIAN ELEKTRODA BATANG TUNGGAL - , Waluyo
The response of grounding systems to impulse is very important effect to power system overvoltage, and can also affect the protective performance of the arresters Under impulse condition, the simple equivalent resistance model is no longer valid for simple rod electrode. When the surge current is high, the electrode system attains very high potential. Because the soils have capacitive and conductive properties, both high current and potential generate high electric field around the rod electrode. Consequently, if electric fields are sufficient magnitudes, it might produce partial breakdown or ionisation of the soil. For these reasons, soil may represent a non linear behaviour. The thesis describes a laboratory experiment in which an impulse source of the capacity of 3kV/3kA peak values is used to inject homogeneous clay soil with controlled moisture contents and densities, electrode dimensions and impulse magnitudes. A cylinder shape container is used to simulate experimentally the electric fields distribution. The non linear behaviour of impulse impedances are showed when the soil moisture is37, 338%, the rod electrode is 1 mm in diameter and vary with its length and impulse magnitude, and the soil density is smallest (1,38 gr/cm3). An aquivalent circuit is derived with EM1P software. The empirical functions have been established for comparison with experiment results. The electrical fields, due to current and potential, are plotted for demonstrating their distribution.